Role of Kefir Milk on The Pathogenesis of Entamoeba histolytica - Mohammed, Sabaa Taher (Iraqi Journal of Science, 2022)
Kefir is fermented milk made from kefir grains consist mainly of lactic acid bacteria and yeast, it has several health-promoting properties, such as antimicrobial ,antitumoral, and immunomodulating effects. However, there are few scientific reports about the effects of kefir on parasites. This work, studied the biological activity of kefir fermented against Entamoeba histolytica parasite in mice at concentration (100% and 50%) compared with the metronidazole (flagyl) drug at concentration (30 mg). The results showed that infected mice treated with kefir(100% and 50%) complete the eradication of parasite after (6th and 8th day) respectively post inoculation while in metronidazole treated group the complete the eradication occur after (8th day) compared with control group which maintain shedding parasite until the end of experiment. The percentage of reduction parasite of treated groups were : kefir 100%was (81.1%) , kefir 50% was (76.4%) and for metronidazole was(75.1%). Histopathological it was study found that the parasite and metronidazole cause mucosal damage and inflammation while kefir reparation of the parasite damage in addition ,notice an increase in INF-γ levels was noticed in serum mice treated with both concentration of kefir and metronidazole reaching (428.8 , 419.8and 442) pg ml respectively compared with a range of positive and negative control, reaching (386.2, 233.2) pg ml. It also caused an increase of the concentration of secretory IgA in the intestinal tissue as it was in kefir groups and metronidazole (5.31 ,4.76 and4.14) ng ml respectively , compared with the positive and negative control groups, reaching (2.91 and 0.72) ng ml respectively. These results indicated that kefir could help in reducing the effect of Entamoeba histolytica or treating the parasite in patients especialy in immune suppressed patients .